1996
DOI: 10.1021/es950326l
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hazardous Substances from Water Using Ultrafiltration in Conjunction with Soluble Polymers

Abstract: The applications of separation techniques using ultrafiltration in connection with functional soluble polymers for the removal of environmentally relevant and toxic substances from waters are reviewed. The types of interactions of the soluble polymers with low molecular mass compounds, the criteria for selecting the appropriate polymeric agents, and the binding conditions are discussed. Several factors influencing the separation of the target substances such as membrane type, solution composition, synergism, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(113 citation statements)
references
References 39 publications
0
110
0
3
Order By: Relevance
“…Of these technologies, the most versatile and widely used is biological denitrification [8] which uses an anoxic environment to completely remove nitrate; the chemically bound oxygen in nitrate acts as a terminal electron acceptor, liberating nitrogen (N 2 ) gas without generating brine as a by-product [9,10,11]. However, membrane filtration has been increasingly used to remove various contaminants from water [12][13][14][15][16]. Tight membrane filtration methods such as reverse osmosis (RO) filtration and nanofiltration (NF) can effectively remove nitrate from contaminated water, but such dense membranes are relatively costly and require electricity.…”
Section: Figure 1 Nitrate Concentrations In Groundwater From 27 Watementioning
confidence: 99%
See 1 more Smart Citation
“…Of these technologies, the most versatile and widely used is biological denitrification [8] which uses an anoxic environment to completely remove nitrate; the chemically bound oxygen in nitrate acts as a terminal electron acceptor, liberating nitrogen (N 2 ) gas without generating brine as a by-product [9,10,11]. However, membrane filtration has been increasingly used to remove various contaminants from water [12][13][14][15][16]. Tight membrane filtration methods such as reverse osmosis (RO) filtration and nanofiltration (NF) can effectively remove nitrate from contaminated water, but such dense membranes are relatively costly and require electricity.…”
Section: Figure 1 Nitrate Concentrations In Groundwater From 27 Watementioning
confidence: 99%
“…Several studies have shown that micellar-enhanced ultrafiltration can effectively remove organic and inorganic pollutants from aqueous phases [12,14,[17][18][19][20][21]. In the present article, we investigate nitrate removal by using three commercially available cross-flow polyethersulfone UF-membranes with different molecular-weight cut-offs (MWCOs).…”
Section: Figure 1 Nitrate Concentrations In Groundwater From 27 Watementioning
confidence: 99%
“…A good review of the area up to 1994 was published by Geckeler and Volchek (1996). A variety of terms and associated acronyms have been used in the literature for this technology including polymer-supported ultrafiltration (PSU) (Geckeler, 1996), liquid-phase polymer-based retention (LPR) (Spivakov, 1989), polyelectolyte-enhanced ultrafiltration (PEUF) (Scamehorn, 1990), and polymer-assisted ultrafiltration (PAUF) (Smith, 1995). The term Polymer Filtration was adopted for this technology by PolyIonix Separation Technologies, Inc., during the course of commercialization activities (Thompson et al, 1999).…”
Section: Polymer Filtration Technologymentioning
confidence: 99%
“…This approach of using water-soluble metal-binding polymers has been in the literature for almost 30 years, but to date no practical application for waste waters has been reported for actinide preconcentration and measurement. 2 We have been developing this analytical separatiodpreconcentration technique for the determination of ultra-low concentrations of alpha-emitting actinides from waste waters.…”
Section: Introductionmentioning
confidence: 99%